UNDERSTANDING HOW PERCEPTION AND LEARNING SATISFACTION SHAPE ACADEMIC PERFORMANCE IN FLIPPED CLASSROOM OBSTETRICS NURSING EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Alias, Zahariah; Mat, Samsiah; Saharin, Amizah; Zakaria, Zaidah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The flipped classroom (FC) model has emerged as a transformative pedagogical strategy in health education, particularly in disciplines that require integrating theoretical knowledge and practical skills. This systematic literature review examines the impact of the FC approach on academic performance, student perceptions, and learning satisfaction in nursing education, with a specific focus on obstetrics contexts. Guided by the PRISMA 2020 protocol and SALSA framework, the review synthesizes findings from 28 peer-reviewed empirical studies published between 2019 and 2025. Articles were identified through Scopus, ScienceDirect, and Google Scholar using Boolean search strings and screened for inclusion based on language, empirical nature, and relevance to nursing education. Thematic and narrative synthesis were employed to categorize findings into three core areas aligned with the research questions. Results demonstrate that the FC model significantly enhances academic performance when implemented with structured pre-class materials and interactive in-class activities. Additionally, students generally perceive the model positively, citing improved engagement and autonomy. Learning satisfaction was found to mediate academic outcomes, highlighting the importance of the quality of instructional design and facilitation. However, gaps remain in the application of FC in specialized areas such as obstetrics nursing, as well as in long-term assessments of clinical competence. This review provides theoretical insights and practical recommendations for nursing educators, curriculum designers, and researchers seeking to optimize learner outcomes through flipped pedagogies.